miR-125b Disrupts Mitochondrial Dynamics via Targeting Mitofusin 1 in Cisplatin-Induced Acute Kidney Injury - Yue Zhao (Karger Publishers, 2021)
Background: Mitochondria are dynamic organelles whose structure are maintained by continuous fusion and fission. During acute kidney injury (AKI) progression, mitochondrial fission in renal tubular cells was elevated, characterized by mitochondrial fragmentation. It is tightly associated with mitochondrial dysfunction, which has been proven as a critical mechanism responsible for AKI. However, the initiating factor for the disruption of mitochondrial dynamics in AKI was not well understood. Objectives: To explore the molecular mechanisms of mitochondrial disorders and kidney damage. Methods: We established cisplatin-induced AKI model in C57BL/6 mice and proximal tubular cells, and detected the expression of miR-125b by qPCR. Then we delivered miR-125b antagomir after cisplatin treatment in mice via hydrodynamic-based gene transfer technique. Subsequently, we performed luciferase reporter and immunoblotting assays to prove miR-125b could directly modulate mitofusin1 (MFN1) expression. We also tested the role of miR-125b in mitochondrial and renal injury through immunofluorescent staining, qPCR, and immunoblotting assays. Results: miR-125b levels were induced in cisplatin-challenged mice and cultured tubular cells. Anti-miR-125b could effectively alleviate cisplatin-induced mitochondrial fragmentation and kidney injury both in vitro and in vivo. Furthermore, miR-125b could directly regulate MFN1, which is a key regulator of mitochondrial fusion. Our study indicated that miR-125b is upregulated during cisplatin-induced AKI. Inhibition of miR-125b may suppress mitochondrial and renal damage through upregulating MFN1. This study suggests that miR-125b could be a potential therapeutic target in AKI.